Approximation to the study of television consumption in the Spanish digital audiovisual ecosystem: from the audiometric audience to the polyhedral audience - Roel, Marta (Estudios sobre el Mensaje Periodístico, 2019)
The linear and non-linear modalities of distribution, management and consumption of television contents in the current digital ecosystem are delimited in order to identify the behavior of the audience in a context of technological innovation, multiplicity of screens and interaction in social networks.
Keywords: Digital television; television consumption; audymetry; social audience.